Performance of Saccharomyces cerevisiae strains against the application of adaptive laboratory evolution strategies for butanol tolerance - Suéllen P.H. Azambuja; Allan H.F. de Mélo; Bruno G. Bertozzi; Heitor P. Inoue; Viviane Y. Egawa; Carlos A. Rosa; Liliana O. Rocha; Gleidson S. Teixeira; Rosana Goldbeck (Food Research International, 2024)

P25-22: Comparison of BMDL calculation performance by the recently developed Bayesian BMD calculation tools using quantal datasets of animal toxicity studies - A. Hirose; Y. Shigeta; T. Kawamura; K. Inoue; M. Matsumoto (Toxicology Letters, 2023)

P03-12: In vivo mutagenicity assessment and derivation of reference dose of styrene - Y. Murata; M. Matsumoto; T. Iso; Y. Shigeta; S. Hasegawa; T. Umano; N. Hirose; K. Horibata; K.-I. Sugiyama; K. Inoue; A. Hirose; K. Masumura (Toxicology Letters, 2023)

Genetic effects of demographic bottleneck and recovery in Kinkazan Island and mainland populations of Japanese macaques (Macaca fuscata) - N. Kazahari; E. Inoue; N. Nakagawa; Y. Kawamoto; T. Uno; M. Inoue-Murayama (Primates, 2023)

Eccrine sweat glands’ maximum ion reabsorption rates during passive heating in older adults (50–84 years) - N. Gerrett; T. Amano; Y. Inoue; Narihiko Kondo (European Journal of Applied Physiology, 2021)

Nanopore sequencing of tomato mottle leaf distortion virus, a new bipartite begomovirus infecting tomato in Brazil - Thais P. Martins; Tadeu A. Souza; Patricia S. da Silva; Erich Y. T. Nakasu; Fernando L. Melo; Alice K. Inoue-Nagata; Tatsuya Nagata (Archives of Virology, 2021)

Complete genome sequence of a new bipartite begomovirus infecting tomato in Brazil - Camila M. Rego-Machado; Erich Y. T. Nakasu; Rosana Blawid; Tatsuya Nagata; Alice K. Inoue-Nagata (Archives of Virology, 2019)

The influence of local skin temperature on the sweat glands maximum ion reabsorption rate - N. Gerrett; T. Amano; G. Havenith; Y. Inoue; Narihiko Kondo (European Journal of Applied Physiology, 2019)

Erratum to: Discovery of two small circular ssDNA viruses associated with the whitefly Bemisia tabaci - Erich Y. T. Nakasu; Fernando L. Melo; Miguel Michereff-Filho; Tatsuya Nagata; Bergmann M. Ribeiro; Simone G. Ribeiro; Cristiano Lacorte; Alice K. Inoue-Nagata (Archives of Virology, 2017)

Spatial variation in low-level 134Cs in the coastal sediments off central Honshu in the Sea of Japan: implications for delivery, migration, and redistribution patterns - Mutsuo Inoue; H. Uemura; H. Kofuji; K. Fujimoto; H. Takata; Y. Shirotani; N. Kudo; S. Nagao (Journal of Oceanography, 2017)

Discovery of two small circular ssDNA viruses associated with the whitefly Bemisia tabaci - Erich Y. T. Nakasu; Fernando L. Melo; Miguel Michereff-Filho; Tatsuya Nagata; Bergmann M. Ribeiro; Simone G. Ribeiro; Cristiano Lacorte; Alice K. Inoue-Nagata (Archives of Virology, 2017)

Factors affecting water availability for high Arctic lichens - T. Inoue; S. Kudoh; M. Uchida; Y. Tanabe; M. Inoue; H. Kanda (Polar Biology, 2017)

Relating food and human hair to assess mercury exposure levels in Poboya, Central Sulawesi, Indonesia - M. M. Sari; T. Inoue; Y. Matsumoto; K. Yokota (International Journal of Environmental Science and Technology, 2017)

Morphological features of an endangered Japanese strain of Cyprinus carpio : reconstruction based on seven SNP markers - K. Atsumi; H. Y. Song; H. Senou; K. Inoue; K. Mabuchi (Journal of Fish Biology, 2017)
Morphological analyses of 183 specimens of Japanese common carp Cyprinus carpio (171 from Lake Biwa and 12 from nursery ponds) using genetic hybrid indices demonstrated that the typical native Japanese strain of C. carpio has a more elongate body, more branched dorsal‐fin rays, fewer and shorter gill rakers, more developed pneumatic bulb, more coiled pneumatic duct, longer posterior swimbladder and shorter intestine than the typical introduced C. carpio . These results provide a basis for a better understanding of the ecological characteristics and taxonomic status of the endangered Japanese strain of C. carpio .

Simultaneous spawning by female stream goby Rhinogobius sp. and the association with brood cannibalism by nesting males - S. Ito; H. Iwao; J. Sakata; M. Inoue; K. Omori; Y. Yanagisawa (Journal of Fish Biology, 2016)
A laboratory experiment was conducted by varying the undersurface area of nesting substratum and the number of females in an experimental tank to elucidate the determinants of the mating pattern in the stream goby, Rhinogobius sp. cross‐band type. Males with larger nests tended to attract two or more females to their nest in a tank. Moreover, males spawned simultaneously with multiple females and entire brood cannibalism by males was rarely observed under a female‐biased sex ratio. When males spawned with a single female with low fecundity, however, entire brood cannibalism occurred at a high frequency, suggesting that a male guarding a nest with fewer eggs consumes the brood. Therefore, spawning behaviour of females that leads to a large egg mass would decrease the risk of entire brood cannibalism. In this species, simultaneous spawning by multiple females in a nest serves as a female counter‐measure against entire brood cannibalism. These results suggest that a conflict of interest between the sexes through brood cannibalism is a major determinant of simultaneous spawning.

A stable and efficient nuclear transformation system for the diatom Chaetoceros gracilis - Kentaro Ifuku; Dongyi Yan; Mado Miyahara; Natsuko Inoue-Kashino; Yoshiharu Y. Yamamoto; Yasuhiro Kashino (Photosynthesis Research, 2015)

The role of the hyporheic zone for a benthic fish in an intermittent river: a refuge, not a graveyard - R. Kawanishi; M. Inoue; R. Dohi; A. Fujii; Y. Miyake (Aquatic Sciences, 2013)

Molecular and biological characterization of a new Brazilian begomovirus, euphorbia yellow mosaic virus (EuYMV), infecting Euphorbia heterophylla plants - Fernanda R. Fernandes; Leonardo C. Albuquerque; Cristiane L. de Oliveira; Andréa R. R. Cruz; Wesley B. da Rocha; Talita G. Pereira; Fernanda Y. B. Naito; Natália de M. Dias; Tatsuya Nagata; Josias C. Faria; Francisco M. Zerbini; Francisco J. L. Aragão; et al. (Archives of Virology, 2011)

Holocene uplifted coral reefs in Lanyu and Lutao Islands to the southeast of Taiwan - S. Inoue; H. Kayanne; N. Matta; W. S. Chen; Y. Ikeda (Coral Reefs, 2011)

Potential for spectral indices to remotely sense phosphorus and potassium content of legume-based pasture as a means of assessing soil phosphorus and potassium fertility status - K. Kawamura; A. D. Mackay; M. P. Tuohy; K. Betteridge; I. D. Sanches; Y. Inoue (International Journal of Remote Sensing, 2011)

Audit and improve! Evaluation of a real-time probe-based PCR assay with internal control for the direct detection of Mycobacterium tuberculosis complex - M. Inoue; W. Y. Tang; S. Y. Wee; T. Barkham (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Temozolomide Delivery to Tumor Cells by a Multifunctional Nano Vehicle Based on Poly(β-L-malic acid) - Rameshwar Patil; José Portilla-Arias; Hui Ding; Satoshi Inoue; Bindu Konda; Jinwei Hu; Kolja A. Wawrowsky; Paul K. Shin; Keith L. Black; Eggehard Holler; Julia Y. Ljubimova (Pharmaceutical Research, 2010)

Enhanced Inhibitory Effects of TBT Chloride on the Development of F1 Rats - H. Asakawa; M. Tsunoda; T. Kaido; M. Hosokawa; C. Sugaya; Y. Inoue; Y. Kudo; T. Satoh; H. Katagiri; H. Akita; M. Saji; M. Wakasa; et al. (Archives of Environmental Contamination and Toxicology, 2010)

Seasonal and interannual variability of oceanic carbon cycling in the western and central tropical-subtropical pacific: A physical-biogeochemical modeling study - Masahiko Fujii; Fei Chai; Lei Shi; Hisayuki Y. Inoue; Masao Ishii (Journal of Oceanography, 2009)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Reflectance characteristics of major land surfaces in slash‐and‐burn ecosystems in Laos - Y. Inoue; J. Qi; A. Olioso; Y. Kiyono; T. Horie; H. Asai; K. Saito; Y. Ochiai; T. Shiraiwa; L. Douangsavanh (International Journal of Remote Sensing, 2008)

Temporal variations in ozone concentrations derived from Principal Component Analysis - S. Yonemura; S. Kawashima; H. Matsueda; Y. Sawa; S. Inoue; H. Tanimoto (Theoretical and Applied Climatology, 2008)

Traceability of slash‐and‐burn land‐use history using optical satellite sensor imagery: a basis for chronosequential assessment of ecosystem carbon stock in Laos - Y. Inoue; J. Qi; A. Olioso; Y. Kiyono; T. Horie; H. Asai; K. Saito; Y. Ochiai; T. Shiraiwa; L. Douangsavanh (International Journal of Remote Sensing, 2007)

Natural infection of Alternanthera tenella (Amaranthaceae) by a new potyvirus - A. M. R. Almeida; C. Y. Fukushigue; F. Sartori; E. Binneck; S. R. R. Marin; A. K. Inoue-nagata; C. M. Chagas; E. R. Souto; T. Mituti (Archives of Virology, 2007)

Evolutionary trend of phylogenetic diversity of nitrogen fixation genes in the gut community of wood‐feeding termites - A. YAMADA; T. INOUE; S. NODA; Y. HONGOH; M. OHKUMA (Molecular Ecology, 2007)
Nitrogen fixation by gut microorganisms is one of the crucial aspects of symbiosis in wood‐feeding termites since these termites thrive on a nitrogen‐poor diet. In order to understand the evolution of this symbiosis, we analysed the nitrogenase structural gene nifH in the gut microbial communities. In conjunction with the published sequences, we compared approximately 320 putatively functional NifH protein sequences obtained from a total of 19 termite samples that represent all the major branches of their currently proposed phylogeny, and from one species of the cockroach Cryptocercus that shares a common ancestor with termites. Using multivariate techniques for clustering and ordination, a phylogeny of NifH protein sequences was created and plotted variously with host termite families, genera, and species. Close concordance was observed between NifH communities and the host termites at genus level, but family level relationships were not always congruent with accepted termite clade structure. Host groups examined included basal families (Mastotermitidae, Termopsidae, Kalotermitidae, as well as Cryptocercus ), the most derived lower termite family Rhinotermitidae, and subfamilies representing the advanced and highly diverse apical family Termitidae (Macrotermitinae, Termitinae, and Nasutitermitinae). This selection encompassed the major nesting and feeding styles recognized in termites, and it was evident that NifH phylogenetic divergence, as well as the occurrence of alternative nitrogenase‐type NifH, was to some extent dependent on host lifestyle as well as phylogenetic position.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Oscillatory behavior of monsoon rainfall over Sri Lanka during the late 19th and 20th centuries and its relationships to SSTs in the Indian Ocean and ENSO - B. A. Malmgren; R. Hullugalla; G. Lindeberg; Y. Inoue; Y. Hayashi; T. Mikami (Theoretical and Applied Climatology, 2007)

Cospeciation in the triplex symbiosis of termite gut protists ( Pseudotrichonympha spp.), their hosts, and their bacterial endosymbionts - S. NODA; O. KITADE; T. INOUE; M. KAWAI; M. KANUKA; K. HIROSHIMA; Y. HONGOH; R. CONSTANTINO; V. UYS; J. ZHONG; T. KUDO; M. OHKUMA (Molecular Ecology, 2007)
A number of cophylogenetic relationships between two organisms namely a host and a symbiont or parasite have been studied to date; however, organismal interactions in nature usually involve multiple members. Here, we investigated the cospeciation of a triplex symbiotic system comprising a hierarchy of three organisms — termites of the family Rhinotermitidae, cellulolytic protists of the genus Pseudotrichonympha in the guts of these termites, and intracellular bacterial symbionts of the protists. The molecular phylogeny was inferred based on two mitochondrial genes for the termites and nuclear small‐subunit rRNA genes for the protists and their endosymbionts, and these were compared. Although intestinal microorganisms are generally considered to have looser associations with the host than intracellular symbionts, the Pseudotrichonympha protists showed almost complete codivergence with the host termites, probably due to strict transmissions by proctodeal trophallaxis or coprophagy based on the social behaviour of the termites. Except for one case, the endosymbiotic bacteria of the protists formed a monophyletic lineage in the order Bacteroidales, and the branching pattern was almost identical to those of the protists and the termites. However, some non‐codivergent evolutionary events were evident. The members of this triplex symbiotic system appear to have cospeciated during their evolution with minor exceptions; the evolutionary relationships were probably established by termite sociality and the complex microbial community in the gut.

Fluctuating serotonergic function in premenstrual dysphoric disorder and premenstrual syndrome: findings from neuroendocrine challenge tests - Y. Inoue; T. Terao; N. Iwata; K. Okamoto; H. Kojima; T. Okamoto; R. Yoshimura; J. Nakamura (Psychopharmacology, 2006)

High incidence of elevated antibody titers to Epstein-Barr virus in patients with uveitis - C. Touge; H. Agawa; T. Sairenji; Y. Inoue (Archives of Virology, 2006)

The phase boundary between wadsleyite and ringwoodite in Mg2SiO4 determined by in situ X-ray diffraction - T. Inoue; T. Irifune; Y. Higo; T. Sanehira; Y. Sueda; A. Yamada; T. Shinmei; D. Yamazaki; J. Ando; K. Funakoshi; W. Utsumi (Physics and Chemistry of Minerals, 2006)

Intracolony variation of bacterial gut microbiota among castes and ages in the fungus‐growing termite Macrotermes gilvus - Y. HONGOH; L. EKPORNPRASIT; T. INOUE; S. MORIYA; S. TRAKULNALEAMSAI; M. OHKUMA; N. NOPARATNARAPORN; T. KUDO (Molecular Ecology, 2006)
The fungus‐growing termites Macrotermes cultivate the obligate ectosymbiontic fungi, Termitomyces . While their relationship has been extesively studied, little is known about the gut bacterial symbionts, which also presumably play a crucial role for the nutrition of the termite host. In this study, we investigated the bacterial gut microbiota in two colonies of Macrotermes gilvus , and compared the diversity and community structure of bacteria among nine termite morphotypes, differing in caste and/or age, using terminal restriction fragment length polymorphism (T‐RFLP) and clonal analysis of 16S rRNA. The obtained molecular community profiles clustered by termite morphotype rather than by colony, and the clustering pattern was clearly more related to a difference in age than to caste. Thus, we suggest that the bacterial gut microbiota change in relation to the food of the termite, which comprises fallen leaves and the fungus nodules of Termitomyces in young workers, and leaves degraded by the fungi, in old workers. Despite these intracolony variations in bacterial gut microbiota, their T‐RFLP profiles formed a distinct cluster against those of the fungus garden, adjacent soil and guts of sympatric wood‐feeding termites, implying a consistency and uniqueness of gut microbiota in M. gilvus . Since many bacterial phylotypes from M. gilvus formed monophyletic clusters with those from distantly related termite species, we suggest that gut bacteria have co‐evolved with the termite host and form a microbiota specific to a termite taxonomic and/or feeding group, and furthermore, to caste and age within a termite species.

Assessment of room temperature influence on finger blood flow response induced by short-term grasping of vibrating handle - M. H. Mahbub; M. Inoue; K. Yokoyama; M. S. Laskar; H. Ohnari; K. Suizu; J. Inagaki; Y. Takahashi; N. Harada (International Archives of Occupational and Environmental Health, 2006)

Pharmacokinetics and pharmacodynamics of etizolam are influenced by polymorphic CYP2C19 activity - T. Fukasawa; N. Yasui–Furukori; A. Suzuki; Y. Inoue; T. Tateishi; K. Otani (European Journal of Clinical Pharmacology, 2005)

Effect of room temperature on percentage finger systolic blood pressure response to finger cooling - M. S. Laskar; K. Ohmura; M. Inoue; K. Yokoyama; J. Inagaki; Y. Takahashi; M. H. Mahbub; H. Ohnari; N. Harada (European Journal of Applied Physiology, 2005)

Effect of skin temperature on the ion reabsorption capacity of sweat glands during exercise in humans - A. K. M. Shamsuddin; T. Kuwahara; A. Oue; C. Nomura; S. Koga; Y. Inoue; N. Kondo (European Journal of Applied Physiology, 2005)

Roles of Volume-sensitive Cl− Channel in Cisplatin-induced Apoptosis in Human Epidermoid Cancer Cells - T. Ise; T. Shimizu; E.L. Lee; H. Inoue; K. Kohno; Y. Okada (The Journal of Membrane Biology, 2005)

Effect of the protein kinase C inhibitor, staurosporine, on the high dose of methamphetamine-induced behavioral sensitization to dizocilpine (MK-801) - Y. R. Fang; T. Abekawa; X. B. Li; Z. C. Wang; T. Inoue; T. Koyama (Psychopharmacology, 2005)

Induction of the metabolism of etizolam by carbamazepine in humans - S. Kondo; T. Fukasawa; N. Yasui-Furukori; T. Aoshima; A. Suzuki; Y. Inoue; T. Tateishi; K. Otani (European Journal of Clinical Pharmacology, 2005)

Findings through the AsiaFlux network and a view toward the future - S. Yamamoto; N. Saigusa; M. Gamo; Y. Fujinuma; G. Inoue; T. Hirano (Journal of Geographical Sciences, 2005)

A novel melon flexivirus transmitted by whitefly - T. Nagata; D. M. T. Alves; A. K. Inoue-Nagata; T.-Y. Tian; E. W. Kitajima; J. E. Cardoso; A. C. de vila (Archives of Virology, 2005)

A novel antipsychotic, perospirone, has antiserotonergic and antidopaminergic effects in human brain: findings from neuroendocrine challenge tests - M. Iwakawa; T. Terao; A. Soya; H. Kojima; Y. Inoue; N. Ueda; R. Yoshimura; J. Nakamura (Psychopharmacology, 2004)

Inhibition of the metabolism of etizolam by itraconazole in humans: evidence for the involvement of CYP3A4 in etizolam metabolism - K. Araki; N. Yasui-Furukori; T. Fukasawa; T. Aoshima; A. Suzuki; Y. Inoue; T. Tateishi; K. Otani (European Journal of Clinical Pharmacology, 2004)

Characterization of Oita virus 296/1972 of Rhabdoviridae isolated from a horseshoe bat bearing characteristics of both lyssavirus and vesiculovirus - K. Tanaka; Y. Sato; S. Morikawa; D. Hayasaka; M. Moriyama; T. Ono; A. Yamada; T. Kurata; T. Iwasaki; S. Inoue; S. Kanai (Archives of Virology, 2004)

Genetic approach to sleep-disordered breathing - Hiroshi KADOTANI; M TANIGUCHI; Y TAKAHASHI; Y INOUE (Sleep and Biological Rhythms, 2004)

Augmented cytoplasmic Smad4 induces acceleration of TGF-?1 signaling in renal tubulointerstitial cells of hereditary nephrotic ICGN mice with chronic renal fibrosis; possible role for myofibroblastic differentiation - Y. Goto; N. Manabe; K. Uchio-Yamada; M. Yamaguchi-Yamada; N. Inoue; Y. Yamamoto; A. Ogura; N. Nagano; H. Miyamoto (Cell and Tissue Research, 2004)

Seasonal Changes in Oceanic pCO2 in the Oyashio Region from Winter to Spring - Takashi Midorikawa; Sonoki Iwano; Kazuhiro Saito; Hiroyuki Takano; Hitomi Kamiya; Masao Ishii; Hisayuki Y. Inoue (Journal of Oceanography, 2003)

Tandem duplication of alkaline phosphatase genes and polymorphism in the intergenic sequence in Bombyx mori - M. Itoh; T. Inoue; Y. Kanamori; S. Nishida; M. Yamaguchi (Molecular Genetics and Genomics, 2003)

The effects of histamine on the lipopolysaccharide-induced metallothionein-I mRNA expression in the mouse spleen - T. Inoue; M. Nakano; N. Oda; T. Yoneyama; Y. Okano; K. Onodera; H. Furuta; C. A. Sogawa; N. Sogawa (Inflammation Research, 2003)

Complete nucleotide sequence of the genomic RNA of Aconitum latent virus (genus Carlavirus) isolated from Delphinium sp. - S. Fuji; H. Yamamoto; M. Inoue; K. Yamashita; Y. Fukui; H. Furuya; H. Naito (Archives of Virology, 2002)

Ecological Evaluation of Gadolinium Toxicity Compared with Other Heavy Metals Using an Aquatic Microcosm - S. Fuma; H. Takeda; K. Miyamoto; K. Yanagisawa; Y. Inoue; N. Ishii; K. Sugai; C. Ishii; Z. Kawabata (Bulletin of Environmental Contamination and Toxicology, 2001)

Enterobacter cowaniisp. nov., a New Species of the Family Enterobacteriaceae - Kohaku Inoue; K. Sugiyama; Y. Kosako; R. Sakazaki; S. Yamai (Current Microbiology, 2000)

Simple Aquatic Microcosm for Ecotoxicity Screening at the Community Level - S. Fuma; H. Takeda; K. Miyamoto; K. Yanagisawa; Y. Inoue; N. Ishii; K. Sugai; C. Ishii; Z. Kawabata (Bulletin of Environmental Contamination and Toxicology, 2000)

A Neurospora Double-Strand-Break repair gene, mus-11, encodes a RAD52 homologue and is inducible by mutagens - Y. Sakuraba; A. L. Schroeder; C. Ishii; H. Inoue (Molecular Genetics and Genomics, 2000)

Hematite in pyrophyllite ore deposits, Shobara district, southwestern Japan - M. Ohkawa; Y. Yamashita; M. Inoue; R. Kitagawa; S. Takeno (Mineralogy and Petrology, 2000)

Subsite-specific risk factors for hypopharyngeal and esophageal cancer (Japan) - T. Takezaki; M. Shinoda; S. Hatooka; Y. Hasegawa; S. Nakamura; K. Hirose; M. Inoue; N. Hamajima; T. Kuroishi; H. Matsuura; K. Tajima (Cancer Causes & Control, 2000)

Role of the pretectal nucleus of the optic tract in short-latency ocular following responses in monkeys - Y. Inoue; A. Takemura; M.J. Mustari; K. Kawano (Experimental Brain Research, 2000)

Two novel mutations of SURF1 in Leigh syndrome with cytochrome c oxidase deficiency - M. Teraoka; Y. Yokoyama; S. Ninomiya; C. Inoue; S. Yamashita; Y. Seino (Human Genetics, 1999)

Physiological significance of hyperpolarization-activated inward currents (I h) in smooth muscle cells from the circular layers of pregnant rat myometrium - K. Okabe; Y. Inoue; T. Kawarabayashi; H. Kajiya; F. Okamoto; H. Soeda (Pflügers Archiv - European Journal of Physiology, 1999)

Two novel mutations of SURF1 in Leigh syndrome with cytochrome c oxidase deficiency - M. Teraoka; Y. Yokoyama; S. Ninomiya; C. Inoue; S. Yamashita; Y. Seino (Human Genetics, 1999)

Physiological significance of hyperpolarization-activated inward currents ( I h ) in smooth muscle cells from the circular layers of pregnant rat myometrium - K. Okabe; Y. Inoue; T. Kawarabayashi; H. Kajiya; F. Okamoto; H. Soeda (Pflügers Archiv - European Journal of Physiology, 1999)

Mg-vacant structural modules and dilution of the symmetry of hydrous wadsleyite, β-Mg 2-x SiH 2x O 4 with 0.00≤x≤0.25 - Y. Kudoh; T. Inoue (Physics and Chemistry of Minerals, 1999)

Exercise- and methylcholine-induced sweating responses in older and younger men: effect of heat acclimation and aerobic fitness - Y. Inoue; George Havenith; W. Larry Kenney; Joseph L. Loomis; Elsworth R. Buskirk (International Journal of Biometeorology, 1999)

Dependence of short-latency ocular following and associated activity in the medial superior temporal area (MST) on ocular vergence - Y. Inoue; A. Takemura; K. Kawano; T. Kitama; F. A. Miles (Experimental Brain Research, 1998)

Histopathological Changes Within the Testis Caused by Allyl Chloride Exposure in Mice - M. Zhao; M. Omura; S. Tokunaga; Y. Romero; N. Inoue (Bulletin of Environmental Contamination and Toxicology, 1998)

Effects of various factors including the CYP2D6 genotype and coadministration of flunitrazepam on the steady-state plasma concentrations of bromperidol and its reduced metabolite - A. Suzuki; K. Otani; K. Mihara; N. Yasui; T. Kondo; N. Tokinaga; H. Furukori; S. Kaneko; Y. Inoue; K. Hayashi (Psychopharmacology, 1998)

The Urinary Excretion of Arsenic Metabolites After a Single Oral Administration of Dimethylarsinic Acid to Rats - K. Yoshida; H. Chen; Y. Inoue; H. Wanibuchi; S. Fukushima; K. Kuroda; G. Endo (Archives of Environmental Contamination and Toxicology, 1997)

Pyruvate alleviates toxic effects of ethanol on cells in culture - K. Fukaya; M. Miyazaki; H. Pu; B. Katayama; Y. Inoue; R. Ohashi; C. Nakamura; M. Namba (Archives of Toxicology, 1997)

Cyclooxygenase inhibitors enhance the production of tissue inhibitor-1 of metalloproteinases (TIMP-1) and pro-matrix metalloproteinase 1 (proMMP-1) in human rheumatoid synovial fibroblasts - S. Takahashi; T. Inoue; M. Higaki; Y. Mizushima (Inflammation Research, 1997)

Interaction between carbamazepine and bromperidol - K. Otani; M. Ishida; N. Yasui; T. Kondo; K. Mihara; A. Suzuki; H. Furukori; S. Kaneko; Y. Inoue (European Journal of Clinical Pharmacology, 1997)

Mapping of transcriptional regulatory domains of pseudorabies virus immediate-early protein - S. Taharaguchi; H. Inoue; E. Ono; H. Kida; S. Yamada; Y. Shimizu (Archives of Virology, 1994)

Identification of epitopes associated with different biological activities on the glycoprotein of vesicular stomatitis virus by use of monoclonal antibodies - S. Nagata; Y. Okamoto; T. Inoue; Y. Ueno; T. Kurata; J. Chiba (Archives of Virology, 1992)

Replication of rat coronavirus in a rat cell line, LBC - N. Hirano; K. Ono; Y. Sada; A. Inoue; T. Murakami; H. Takamaru (Archives of Virology, 1985)

Morphology of SMON virus - Hiroko Bessho; Yoko Nishibe; Y. K. Inoue (Archives of Virology, 1974)

Relationship between SMON virus and avian infectious laryngotracheitis virus - Yoko Nishibe; Y. K. Inoue (Archives of Virology, 1974)

Properties of virus associated with subacute myelo-optico-neuropathy - Yoko Nishibe; T. Kimura; Y. K. Inoue (Archives of Virology, 1973)

A toxic substance produced by Japanese encephalitis virus in mouse brain - Kyosuke Ozawa; Y. Kanda Inoue (Archives of Virology, 1973)

Clonal analysis of tumorigenesis of bovine adenovirus type 3 and isolation of a nontumorigenic variant - Y. Nishibe; T. Kimura; Y. K. Inoue (Archives of Virology, 1970)

The experimental production of a formalin-killed Japanese encephalitis virus vaccine from porcine kidney cell cultures - Y. Kanda Inoue; Yobo Nishibe (Archives of Virology, 1967)

An improved method of assay for human adenovirus type 12 (prototype strain) employing a clonal line of porcine kidney cells - Y. Kanda Inoue; Yoko Nishibe (Archives of Virology, 1966)